2011
DOI: 10.3858/emm.2011.43.2.020
|View full text |Cite
|
Sign up to set email alerts
|

Iron mediates endothelial cell damage and blood-brain barrier opening in the hippocampus after transient forebrain ischemia in rats

Abstract: Blood cells are transported into the brain and are thought to participate in neurodegenerative processes following hypoxic ischemic injury. We examined the possibility that transient forebrain ischemia (TFI) causes the blood-brain barrier (BBB) to become permeable to blood cells, possibly via dysfunction and degeneration of endothelial cells in rats. Extravasation of Evans blue and immunoglobulin G (IgG) was observed in the hippocampal CA1-2 areas within 8 h after TFI, and peaked at 48 h. This extravasation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 43 publications
2
56
0
1
Order By: Relevance
“…Further, it has been reported that both VEGF-A and VEGF-C can induce formation of receptors heterodimers (VEGFR-2/ VEGFR-3) in addition to homodimers and can exert their biological responses (Dixelius et al, 2003;Nilsson et al, 2010). Moreover, the bioavailability of SAR131675 in the brain is also not known, although it has been reported that transient forebrain ischemia can open the blood-brain barrier in the hippocampus which facilitates entering of small molecule drugs into the brain (Won et al, 2011). Therefore, future investigations are needed to examine the bioavailability of VEGFR-3 inhibitors in the brain and the possible effect of VEGFR-3 inhibitors on VEGF-A signaling in the ischemic tolerance paradigm as well.…”
Section: Discussionmentioning
confidence: 96%
“…Further, it has been reported that both VEGF-A and VEGF-C can induce formation of receptors heterodimers (VEGFR-2/ VEGFR-3) in addition to homodimers and can exert their biological responses (Dixelius et al, 2003;Nilsson et al, 2010). Moreover, the bioavailability of SAR131675 in the brain is also not known, although it has been reported that transient forebrain ischemia can open the blood-brain barrier in the hippocampus which facilitates entering of small molecule drugs into the brain (Won et al, 2011). Therefore, future investigations are needed to examine the bioavailability of VEGFR-3 inhibitors in the brain and the possible effect of VEGFR-3 inhibitors on VEGF-A signaling in the ischemic tolerance paradigm as well.…”
Section: Discussionmentioning
confidence: 96%
“…Supporting this fact, it has been found that iron depositions are observed close to vessels, which may be inducing an elevated BBB damage. 15,29 Finally, we have also found more severe HT and increased hemorrhage-related parameters when reperfusing with tPA as soon as 1 hour after ischemia in animals with iron overload. In this context, it is difficult to discriminate whether the bleeding induced after tPA administration is because of tPA or reperfusion.…”
Section: Strokementioning
confidence: 70%
“…Ischemia and subsequent reperfusion leads to effects on the blood brain barrier resulting in alterations in iron homeostasis (Won et al, 2011) which must be efficiently regulated to preclude free radical-mediated reactions that can be potent drivers of inflammation and ultimately cell death (Dang et al, 2011;Salvador, 2010). Both Fth1/ferritin and Tf/transferrin have high affinities for free iron and are thus responsible for sequestering this redox promoting ion (Wang and Pantopoulos, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Iron metabolism and homeostasis following ET-1 treatment of the MCA Transient ischemia has been shown to result in iron overload and mitochondrial free radical production through increased permeability of the blood brain barrier (Won et al, 2011). The importance of iron homeostasis has also been indirectly shown based on the increased tolerance against cerebral ischemia associated with iron chelation by desferoxamine (Prass et al, 2002).…”
Section: 4mentioning
confidence: 99%